2018
DOI: 10.1002/tal.1559
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table tests on braced reinforced concrete frame structure across the earth fissure under earthquake

Abstract: A series of shaking table tests on a scaled model were conducted to investigate the effect of steel braces on reinforced concrete frame structure across earth fissure under earthquake. In the test, a 1/15 scaled model structure taking into account soil-structure interaction was designed on the basis of similarity theorem. Seismic response data, including acceleration responses, displacement responses, shear force distributions, and strain amplitudes of column reinforcement were obtained and analyzed by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Based on the derived similarity ratios, this study employed particle concrete and galvanized iron wire for constructing the model framework. Particle concrete and galvanized iron wire have found extensive use in similar model experiments [ 36 ]. Numerous numerical simulation studies have demonstrated their effectiveness in simulating the properties of concrete and reinforcement steel.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…Based on the derived similarity ratios, this study employed particle concrete and galvanized iron wire for constructing the model framework. Particle concrete and galvanized iron wire have found extensive use in similar model experiments [ 36 ]. Numerous numerical simulation studies have demonstrated their effectiveness in simulating the properties of concrete and reinforcement steel.…”
Section: Experimental Setupsmentioning
confidence: 99%